Expanding pancreas donor pool by evaluation of unallocated organs after brain death: Study protocol clinical trial (SPIRIT Compliant). Issue 10 (March 2020) - Kulu, Yakup; Khajeh, Elias; Ghamarnejad, Omid; Nikdad, Mohammadsadegh; Sabagh, Mohammadsadegh; Ali-Hasan-Al-Saegh, Sadeq; Nadalin, Silvio; Quante, Markus; Pisarski, Przemyslaw; Jänigen, Bernd; Reißfelder, Christoph; Mieth, Markus; et al.
Abstract: Background: Pancreas graft quality directly affects morbidity and mortality rates after pancreas transplantation (PTx). The criteria for pancreas graft allocation are restricted, which has decreased the number of available organs. Suitable pancreatic allografts are selected based on donor demographics, medical history, and the transplant surgeon's assessment of organ quality during procurement. Quality is assessed based on macroscopic appearance, which is biased by individual experience and personal skills. Therefore, we aim to assess the histopathological quality of unallocated pancreas organs to determine how many unallocated organs are potentially of suitable quality for PTx. Methods and analysis: This is a multicenter cross-sectional explorative study. The demographic data and medical history of donor and cause of rejection of the allocation of graft will be recorded. Organs of included donors will be explanted and macroscopic features such as weight, color, size, and stiffness will be recorded by 2 independent transplant surgeons. A tissue sample of the organ will be fixed for further microscopic assessments. Histopathologic assessments will be performed as soon as a biopsy can be obtained. We will evaluate up to 100 pancreata in this study. Result: This study will evaluate the histopathological quality of unallocated pancreas organs from brain-dead donors to determine how many of these unallocated organs were potentially suitable for transplantation based on a histopathologic evaluation of organ quality. Conclusion: The comprehensive findings of this study could help to increase the pancreas graft pool, overcome organ shortage, reduce the waiting time, and also increase the number of PTx in the future. Registration number: ClinicalTrials.gov: NCT04127266